The Comparative Textual Criticism of Religious Scriptures - Driesbach, Jason K. ,; Finsterbusch, Karin,; Fuller, Russell E.,; Lange, Armin, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
This collection of articles uniquely brings into scholarly dialogue the textual history and criticism of authoritative literatures from diverse cultures: they study Mesopotamian literature, the Hebrew Bible, the New Testament, the Homeric epics, the Quran, and Hindu and Buddhist literatures with an interest in all matters of their textual transmission. Contributors address questions such as: What role does textual criticism play in the study of authoritative texts in these fields? How much variation exists in these textual traditions? Can you observe processes of textual standardization? What role does the oral transmission play? How are critical editions prepared? While these questions have produced a wealth of scholarly literature for each individual field, this volume is the first to study them from a comparative perspective.